The Ethics of Dealing with the Other, in the Thought of Prince El-Amir Abdelkader Al-Jazairi - مزهود سليم (Milev Journal of Research and Studies, 2020)
This article aims to clarify the ethics of the convivial and behaviour with other in the thought of El-Amir Abdelkader Al-Jazairi, that gained him a high standing throughout history, until the enemy and friend confess by him , especially since El-Amir Abdelkader have a tolerant human ethics in adversity and when he is in a position of power, which contributed to spreading the idea of ​​peaceful coexistence and consolidating human rights principles before the birth of United Nations, which later taken many of these ethics. The question: What are these morals and principles, and where did they appear?To answer the question, the article is subject to the descriptive method.